Pelaksanaan Program "Cek Tensi dan Gula Darah Gratis" oleh KKN Kelompok 14 Universitas Abdurrab di Tembilahan - Qonaah Ulfa Nurrahmah; Fitri Lestari; Melvia Tri Yunita; Bintang Indragiri; Luthfiyyah Ananda Putri; Suci Tiara Pertiwi; Mayada Fahrina; Epa Arnas; Ridiani Maulia; Anindya Wulan; Tika Rahmawina; Fitria Fitria; Mawaddah Muthia Amanda; Mutia Rahmawati; Muhammad Kevin Naufal Sakti; M.Daffa Naufalsyah; Juliana Tanjung; Muh.Rizki; Tia Oktiani; Seri Widiyana (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
This activity aims to increase public health awareness through free blood pressure and blood sugar check services. The activity was carried out on Car Free Day (CFD) in Tembilahan, Jl. Swarna Bumi, by KKN Group 14 of Abdurrab University. The community who attended not only received health services, but also information about Abdurrab University through the distribution of brochures. The methods used were direct service and health education. The results showed high enthusiasm from the community with 100 participants checking their blood pressure and 80 participants checking their blood sugar. This program succeeded in increasing basic public health knowledge and improving the positive image of the university.